Structure of passive voice in kalakche sub-dialect - Hajjy, Mahir; Abuzeid, Sanya (Humanities Journal of University of Zakho, 2023)
This research entitled “ Structure of Passive Voice in Kalakche Sub-dialect " in which the syntactic formation of the passive voice of this area. is generally covered and chosen the formation rules and syntactic features are analyzed. The significance of this research lies in referring to passive voice of Kalakche sub- dialect for In this study, the descriptive analysis approach. is employed as well as the subject is explained and the formation of and Passive is covered. past Present. What are the syntactic features of agent in Kalakche sub-dialect? How forms does passive voice many this passive voice agent have in this sub-dialect of? Is this agent Formed Syntactically or morphologically? or either way? research is done on the Kurdish language Kalakche sub- dialect. The data is collected from the everyday language of the area. Finally, the conclusions of this research are shown.